Consumption sacrifice - Garcia‐Rada, Ximena; Kim, Tami; Liu, Peggy J. (Journal of Consumer Psychology, 2025)
AbstractMuch marketing research focuses on what individual consumers need or want for consumption and how they satisfy these needs or wants themselves. However, consumers often give up money, time, or preferences to help others address their consumption needs and wants across the customer journey. The authors introduce the unifying construct of “consumption sacrifice,” defined as the willing and intentional act of incurring a cost to the self—in money, time, or preferences—when making a consumption decision, with expected direct benefits to one's partner. The authors offer examples of consumption sacrifices along the customer journey and suggest that this construct offers a new lens through which to examine the existing literature on choices involving others. The authors put forward the view that sacrifices are often invisible to recipients—and thus underrecognized and underappreciated—failing to achieve their full potential. At the same time, different sacrifice motives (partner‐focused, relationship‐focused, self‐focused) may affect the extent to which actors care about making sacrifices visible to recipients. Finally, the authors propose future research questions, including what leads consumers to perform more visible sacrifices, what drives the invisibility of sacrifices among recipients, and what are the consequences of performing and receiving invisible sacrifices.